2013
DOI: 10.5915/44-1-9988
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Trial of Jawarish Amla as Adjuvant to Anti-Tubercular Treatment Drugs for Control of Adverse Reactions in DOTS Regime in Pulmonary TB Patients

Abstract: Background and objectivesOne of the greatest challenges of health care systems at the dawn of the 21st century is tuberculosis (TB). Drug resistant strains of TB are becoming a global public health risk. These strains commonly appear due to faulty therapies. Patients frequently stop treatment due to the toxicity of anti-tubercular treatment (ATT) drugs. Amla (Emblica officinalis) is a well-known Unani single drug. Jawarish amla is a Unani compound formulation which is commonly used to administer amla. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Calculate the number of cells per ml, and the total number of cells, using the following formula 71 . Calculate percent viability by using the formula: Principle of MTT Assay: This Colorimetric assay is based on the capacity of Mitochondria succinate dehydrogenase enzymes in living cells to reduce the yellow water-soluble substrate 3(4, 5dimethyl thiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) into an insoluble, colored formazan product which is measured spectrophotometrically 19,20 . Since the reduction of MTT can only occur in metabolically active cells, the level of activity is a measure of the viability of the cells.…”
Section: Methods Of Trypan Blue Dye Exclusion Methodmentioning
confidence: 99%
“…Calculate the number of cells per ml, and the total number of cells, using the following formula 71 . Calculate percent viability by using the formula: Principle of MTT Assay: This Colorimetric assay is based on the capacity of Mitochondria succinate dehydrogenase enzymes in living cells to reduce the yellow water-soluble substrate 3(4, 5dimethyl thiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) into an insoluble, colored formazan product which is measured spectrophotometrically 19,20 . Since the reduction of MTT can only occur in metabolically active cells, the level of activity is a measure of the viability of the cells.…”
Section: Methods Of Trypan Blue Dye Exclusion Methodmentioning
confidence: 99%
“…Distinctly, the processing methods of Ayurvedic medicinal materials also include frying, soaking and steaming, which is similar to the TCM processing methods. An example of a medicinal material (Phyllanthus emblica, commonly known as Amla in India) used with different processing methods in different systems of Indian medicine is indicated in Table 5 (Srivasuki, 2012;Anonymous, 2007;Sherwani et al, 2012).…”
Section: Processing Methodsmentioning
confidence: 99%
“…Recently, immunomodulatory and anti-mycobacterial activities of JAS available in the market have been reported. [3,4] Literature survey revealed that the formulation composition of the marketed formulation varies significantly in terms of the number as well as the percent component of ingredients. In order to have uniform quality as well as batch to batch consistency, there is an urgent need to have some reference standards for quality control and standardization of this formulation.…”
Section: The Formulation Includes Six Medicinal Herbs Namelymentioning
confidence: 99%